Intervención del terapista respiratorio en paciente masculino de 82 años de edad con diagnóstico de neumonía bacteriana adquirida en la comunidad. - Piguabe Bravo, Tatiana Lisseth (2022)
The focus of this study is based on the intervention of the respiratory therapist in an 82-year-old male patient diagnosed with bacterial pneumonia. Community-acquired bacterial pneumonia is one of the main lung diseases affecting older adults and children around the world. This pathology is mainly caused by the bacteria Streptococcus pneumoniae. Bacterial pneumonia acquired in the community in our country in the last 5 years is considered a serious health problem because it is among the 4 leading causes of morbidity in pediatric patients and in the elderly, being one of the main reasons for consultation and hospital admissions in the different hospitals of the country. The main risk factor that triggers community-acquired bacterial pneumonia in the 82-year-old patient is due to the fact that he is an active smoker, 2 packs of cigarettes a day, in addition to the pathogenic microorganisms found in the environment that produce said pneumonia. illness.